1997
DOI: 10.1073/pnas.94.6.2741
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin stimulates the release of luteinizing hormone-releasing hormone from medial basal hypothalamic explants by releasing nitric oxide

Abstract: Oxytocin induces mating behavior in rats of both sexes. Previous experiments revealed that progesteroneinduced sex behavior in ovariectomized, estrogen-primed rats was caused by release of NO from NOergic neurons that stimulated the release of luteinizing hormone-releasing hormone (LHRH). The LHRH activated brain-stem neurons that initiated the lordosis ref lex. We hypothesized that oxytocin might similarly release NO in the medial basal hypothalamic region that would stimulate release of LHRH into the hypophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 16 publications
4
37
1
Order By: Relevance
“…However, at least, suppression of LH surges in pup-removed lactating rats is not attributable to blockade of oxytocin action at the pituitary level, because the primary cause of the suppression of LH surges by pup removal is at the hypothalamic level, i.e., it is attributable to the failure of activation of the GnRH surge generator in the hypothalamus as evidenced by the GnRH/c-Fos immunohistochemical studies. On the other hand, several studies have demonstrated the central action of oxytocin on GnRH release (Rettori et al 1994, Selvage & Johnston 2001. These findings may support our conclusion regarding the involvement of Photomicrographs showing c-Fos-positive GnRH neurons in lactating rats.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, at least, suppression of LH surges in pup-removed lactating rats is not attributable to blockade of oxytocin action at the pituitary level, because the primary cause of the suppression of LH surges by pup removal is at the hypothalamic level, i.e., it is attributable to the failure of activation of the GnRH surge generator in the hypothalamus as evidenced by the GnRH/c-Fos immunohistochemical studies. On the other hand, several studies have demonstrated the central action of oxytocin on GnRH release (Rettori et al 1994, Selvage & Johnston 2001. These findings may support our conclusion regarding the involvement of Photomicrographs showing c-Fos-positive GnRH neurons in lactating rats.…”
Section: Discussionsupporting
confidence: 82%
“…This hypothesis is based on the finding that suckling induces oxytocin release and oxytocin regulates LH secretion by acting at the hypothalamic level (Rettori et al 1994, Selvage & Johnston 2001. To mimic oxytocin release in response to the suckling stimulus, oxytocin was intracerebroventricularly injected into nonsuckled and, therefore, LH surge-suppressed rats.…”
Section: Effect Of Icv Injections Of Oxytocin On Pup Removal-inducmentioning
confidence: 99%
“…These glutamergic neurons appear to play a physiological role in the preovulatory release of LHRH by stimulating the noradrenergic neurons. Oxytocin similarly stimulates these neurons; therefore, there is a multisynaptic input to the noradenergic terminals that brings about a large increase in NO release that is responsible for the preovulatory surge of LHRH (14). We hypothesize that the inhibitory ␤-endorphinergic input into the system uses this NOergic pathway.…”
mentioning
confidence: 99%
“…NO functions as a neurotransmitter (2)(3)(4)(5)(6)(7)(8)(9)(10) and nNOS is present near gonadotropin-releasing hormone terminals (14) and in regions of the brain that appear to regulate emotional behaviors (15,16). Estradiol (E 2 ) up-regulates endothelial NOS in endothelial cells (17,18) and nNOS in the brain (18)(19)(20)(21), and many of the actions of E 2 on the brain have been suggested to be through a NO-mediated mechanism (2)(3)(4)(5)(6)(7)(8)(9)(10)(18)(19)(20)(21)(22). Administration of E 2 and progesterone to ovariectomized rats leads to an increase in the luteinizing hormone surge, the magnitude of which is significantly attenuated after administration of nNOS antisense oligonucleotides into the third ventricle (22), suggesting an intermediary role of NO in modulating some actions of E 2 by up-regulating nNOS activity.…”
mentioning
confidence: 99%